2020
DOI: 10.1038/s41598-020-58467-9
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Models for Histopathological Classification of Gastric and Colonic Epithelial Tumours

Abstract: Histopathological classification of gastric and colonic epithelial tumours is one of the routine pathological diagnosis tasks for pathologists. Computational pathology techniques based on Artificial intelligence (AI) would be of high benefit in easing the ever increasing workloads on pathologists, especially in regions that have shortages in access to pathological diagnosis services. In this study, we trained convolutional neural networks (cnns) and recurrent neural networks (Rnns) on biopsy histopathology who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
325
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 343 publications
(326 citation statements)
references
References 30 publications
(31 reference statements)
1
325
0
Order By: Relevance
“…There are several deep learning models that have been developed for the diagnostic of gastric cancers using whole slide images (11)(12)(13)15,24) and a comparison of some of these studies and ours is summarized in Supplementary Table S9. Although each study adopted a results of 0.97-0.99 AUROC in the prospective set.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several deep learning models that have been developed for the diagnostic of gastric cancers using whole slide images (11)(12)(13)15,24) and a comparison of some of these studies and ours is summarized in Supplementary Table S9. Although each study adopted a results of 0.97-0.99 AUROC in the prospective set.…”
Section: Discussionmentioning
confidence: 99%
“…Iizuka et al evaluated their algorithm that classifies WSIs into either non-neoplastic, adenoma, or adenocarcinoma, and confirmed accuracy of 95.6% from their test set consisting of 45 WSIs. (13) Although the aforementioned CNN-based gastric cancer detection algorithms have shown promising results, their diagnostic performance in the real clinical setting as well as impact on diagnostic workflow has not been validated.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, CNNs are applied not only in digital pathology, but also in computed tomography (CT) scans, ophthalmoscope images, and ultrasound images ( Esteva et al, 2017 ; De Fauw et al, 2018 ; Coudray et al, 2018 ; Philbrick et al, 2018 ; Falk et al, 2019 ; Li et al, 2019 ). Studies ( Macenko et al, 2009 ; Iizuka et al, 2020 ) have revealed that AI can identify various lesions with a level of competence observed by imaging experts.…”
Section: Discussionmentioning
confidence: 99%
“…A simple CNN architecture for automatic classification of GC using WSIs in histopathology has been described by Sharma et al ( Sharma et al, 2017b ), thereby revealing the practicability of AI in digital-pathology research for GC. However, their work has rarely focused on how the deep-learning framework identifies GC lesions, nor how the results might influence the prognosis ( Droste et al, 2019 ; Iizuka et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…(14)(15)(16) This expands upon our preliminary model, as with the use of ResNet50 it provides powerful analytics for images. Further, the input to the previously published model (30) and other similar published studies for other clinical diseases consisted of small patches of whole slide images (15,34) that represent approximately 2% of the original biopsy image. Such patch inputs do not take into account the fact that tissue features can be better visualized at multiple magnifications.…”
Section: Discussionmentioning
confidence: 99%